Evaluation of CDC-Recommended Approaches for Confirmatory Testing of Positive Neisseria gonorrhoeae Nucleic Acid Amplification Test Results - Moncada, Jeanne (American Society for Microbiology (ASM), 2008)
We evaluated three of the CDC approaches for confirming Neisseria gonorrhoeae (gonococcus [GC])-positive nucleic acid amplification test (NAAT) results: (i) repeating the original test on the original specimen, (ii) testing the original specimen with a different test, and (iii) performing a different test on a duplicate specimen collected at the same visit. For the first approach, clinical specimens were initially tested by Aptima Combo 2 (AC2) (Gen-Probe Inc., San Diego, CA), ProbeTec (strand displacement amplification [SDA]) (Becton Dickinson Co., Sparks, MD), and Amplicor (PCR) (Roche Molecular Systems, Branchburg, NJ). The original GC-positive specimens were then retested by the same NAAT for confirmation. For the second approach, specimens initially positive by AC2, SDA, or PCR were retested by different NAATs (SDA, PCR, AC2, and Aptima Neisseria gonorrhoeae assay [AGC]; Gen-Probe Inc.). For the third approach, duplicate urethral swabs and first-catch urine (FCU) samples from men and duplicate cervical swabs and FCU samples from women were each tested by SDA, AC2, and AGC in parallel. We found that 89 to 96% of samples positive by SDA, PCR, and AC2 were confirmed by repeat testing and that 85 to 98% of SDA, PCR, and AC2 results were confirmed by using different NAATs on the original specimen. For FCU samples from men, any NAAT can be used for confirmation. However, for all other specimen types, some NAATs cannot be used to confirm positive results from other NAATs. Thus, a single repeat test appears to be a reliable method for confirmation, but by doing more extensive testing, an additional 5% were confirmed. With >90% of all GC-positive NAATs being confirmed, our results show that confirmatory testing is not warranted for these genital specimens.